THE PROFILE OF PHYSICAL PROBLEM-SOLVING BASED ON STUDENT’S PERSONALITY TYPES - Alfathy, Ragil Meita; Astuti, Budi; Linuwih, Suharto (Universitas Negeri Semarang, 2019)
Problem solving is important for learning physics at any level which involves the process of analysing, interpreting, reasoning, predicting, evaluating and reflecting. However, researches about problem-solving strategies or techniques based on students? personality have not been widely practiced. This strategy is important to be studied based on thoughts, characters and actions of students. Therefore, the aims of the research are to connect students problem solving of physics based on their personality and identify students problem solving pattern based on their personality according to The Four Temperament Theory of Keirsey (1998). The method used in this research is descriptive qualitative research with the type of Investigation of Lived Experience that explores inner experiences (Gall et al, 2003). Subjects in this study are 12th grade students of science class program of MAN 1 Banyumas which is determined by stratified sampling approach. They were divided into homogeneous groups. The grouping is based on Keirsey's four personality types: Idealist, Artisan, Guardian and Rational. Each personality type, selected nine students as research subjects are determined using purposive sampling technique. The results showed that the strategy of physics problem solving of Idealist type was conceptual problem solving, Artisan type used intuitive-analogic for solving the problem, Guardian type used intuitive for solving the problem, and Rational type used analogic strategy for solving the problem.